2006
DOI: 10.1007/s11434-006-2213-y
|View full text |Cite
|
Sign up to set email alerts
|

A new measure to characterize multifractality of sleep electroencephalogram

Abstract: Traditional methods for nonlinear dynamic analysis, such as correlation dimension, Lyapunov exponent, approximate entropy, detrended fluctuation analysis, using a single parameter, cannot fully describe the extremely sophisticated behavior of electroencephalogram (EEG). The multifractal formalism reveals more "hidden" information of EEG by using singularity spectrum to characterize its nonlinear dynamics. In this paper, the zero-crossing time intervals of sleep EEG were studied using multifractal analysis. A n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 18 publications
(19 reference statements)
0
15
2
Order By: Relevance
“…Fractal properties of the human sleep EEG have already been investigated by other research groups (Pereda et al, 1998;Shen et al, 2003;Lee et al, 2004;Acharya et al, 2005;Ma et al, 2006;Leistedt et al, 2007a,b), however, these studies were limited by low sampling rate (100 Hz in Acharya et al, 2005;Ma et al, 2006;Leistedt et al, 2007a,b;128 Hz in Shen et al, 2003) or low number of EEG channels (Fpz-Cz and Pz-Cz in Acharya et al, 2005;Ma et al, 2006;Cz in Leistedt et al, 2007a,b;C3 in Pereda et al, 1998;Shen et al, 2003;C4 in Lee et al, 2004). To assess MOF properties Pereda et al (1998) estimated the fractal exponentˇusing coarse grain spectral analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fractal properties of the human sleep EEG have already been investigated by other research groups (Pereda et al, 1998;Shen et al, 2003;Lee et al, 2004;Acharya et al, 2005;Ma et al, 2006;Leistedt et al, 2007a,b), however, these studies were limited by low sampling rate (100 Hz in Acharya et al, 2005;Ma et al, 2006;Leistedt et al, 2007a,b;128 Hz in Shen et al, 2003) or low number of EEG channels (Fpz-Cz and Pz-Cz in Acharya et al, 2005;Ma et al, 2006;Cz in Leistedt et al, 2007a,b;C3 in Pereda et al, 1998;Shen et al, 2003;C4 in Lee et al, 2004). To assess MOF properties Pereda et al (1998) estimated the fractal exponentˇusing coarse grain spectral analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Pereda et al (1998) also found higherˇvalues for deeper sleep stages. Ma et al (2006) assessed MUF properties of the sleep EEG estimating the range of the singularity strength and the asymmetry of the singularity spectrum. These measures also correlated with the sleep depth, exhibiting higher values for deeper sleep stages.…”
Section: Introductionmentioning
confidence: 99%
“…Results of one sample sc4002e0 are presented in Figure 4 as an example, where Figure 4(a) gives the artificially judged hypnogram provided by the database according to Rechtschaffen and Kales (R&K) criterion [30], among which Wake denotes clear state, S1-S4 express gradually deepening sleep stages from degree 1 to 4, and REM represents rapid eye movement period. Arrows in this figure point out locations of sudden awakening during the course of sleep [15]. Figures 4(b) and (c) are the exhibitions calculated from K τ(q) and Δα respectively, which suggest that these indicators can all make good judgments on the above sleep states.…”
Section: Application Of K τ(Q) To Eeg Time Seriesmentioning
confidence: 92%
“…Since the conception of multifractal structure was first reported in 1986 by Halsey et al [5], it had been uncovered and greatly developed in a number of classical realms of science. In biology, important conclusion has been drawn, such as to the studies of DNA sequences [6,7], heartbeat information [8][9][10][11][12][13], cerebral electrical signals [14,15] and so on.…”
mentioning
confidence: 99%
“…Nevertheless, existing data also suggest that a single parameter or fractal dimension may be insufficient to characterize such complicated behaviors as human bioelectrical activities. Because of their multiple dimensions, multifractal theories [5][6][7][8][9][10][11][12][13][14][15][16] are more effective for examining the diverse levels of the fractal system.…”
mentioning
confidence: 99%